The Role of Pancasila and Civic Education in Shaping Tolerance and Bhineka Tunggal Ika Attitudes Among Generation Z at Muhammadiyah Junior High School in Palangka Raya - Mahendra, Irvan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to explore the role of Pancasila and Citizenship Education (PPKn) in shaping attitudes of tolerance and the values ​​of Bhineka Tunggal Ika (Unity in Diversity) in Generation Z students at Muhammadiyah Junior High School Palangka Raya. This study used a qualitative approach with a case study design involving 13 informants, consisting of 9 students (grades VII, VIII, and IX), 2 PPKn teachers, 1 school counselor, and 1 administrative staff. Data collection techniques included in-depth interviews, participant observation, and document analysis. Data were analyzed using a thematic approach with the stages of transcription, coding, identification of main themes, interpretation of findings, and preparation of narrative descriptions. The results showed that PPKn learning played a significant role in internalizing Pancasila values ​​through group strategy discussions, contextual examples, and reflection activities. Students' attitudes of tolerance were formed through formal learning and social interactions in the school environment, with the level of understanding developing according to grade level. Reinforcement of the Bhineka Tunggal Ika value was strengthened through a school culture that supports diversity, flag ceremonies, national day commemorations, and collaborative projects. Exemplary teachers, supportive guidance and counseling services, and inclusive school policies create a conducive educational environment for student character development. This study confirms that PPKn serves as an important vehicle for instilling the values ​​of tolerance and Bhinneka Tunggal Ika (Unity in Diversity) in Generation Z, emphasizing the need to strengthen meaningful learning supported by a consistent school culture to develop citizens capable of living harmoniously in a multicultural society and possessing a strong commitment to national unity.